Cover Image. Issue 4 (29th July 2020) - Serup, Jørgen; Grove, Gary; ,; Querleux, Bernard; Hawkins, Stacy; El Gammal, Stephan; Fluhr, Joachim; Koenig, Karsten; Wilhelm, Klaus-Peter; Houser, Tim; Muizzuddin, Neelam; Tate, Margaret; et al.
Abstract : The cover image is based on Professor Ronald Marks of Cardiff (1935‐2020), founder of the research field bioengineering and the skin and the International Society for Bioengineering and the Skin (ISBS) formed in 1979. https://doi.org/10.1111/srt.12904 .